Insights into lattice oxygen and strains of oxide-derived copper for ammonia electrosynthesis from nitrate - Qinyue Wu; Xinfei Fan; Bing Shan; Liang Qi; Xie Quan; Yanming Liu (Nature Communications)
Abstract Electrocatalytic NO3 − reduction (eNO3RR) is a sustainable method for purification of NO3 − wastewater and NH3 recovery. Cu-based catalysts are promising for eNO3RR, but insufficient active hydrogen (*H) supply and *NO2 poison of active sites have hindered their performance, and the catalytic mechanism remains ambiguous. Here, we report oxide-derived copper nanosheet arrays (OD-Cu NSs) with residual lattice oxygen and lattice strains to enhance NH3 synthesis from eNO3RR. It is efficient for NH3 synthesis with high Faradaic efficiencies of 88.7-99.7% and maximum NH3 yield of 6.20 mmol·h−1·cm−2 at neutral solution, 10-140 mM NO3 − and 50-1500 mA·cm−2. Experimental and theoretical results reveal that lattice oxygen regulates the electronic structure of OD-Cu NSs and promotes *NO2 conversion, while lattice strain enhances *H generation from water dissociation, resulting in the good performance for NH3 synthesis. The applicability of OD-Cu NSs is proved by the high recovery of ammonia compound from eNO3RR.